2017
DOI: 10.1152/ajprenal.00012.2017
|View full text |Cite
|
Sign up to set email alerts
|

Insulin stimulates uric acid reabsorption via regulating urate transporter 1 and ATP-binding cassette subfamily G member 2

Abstract: Accumulating data indicate that renal uric acid (UA) handling is altered in diabetes and by hypoglycemic agents. In addition, hyperinsulinemia is associated with hyperuricemia and hypouricosuria. However, the underlying mechanisms remain unclear. In this study, we aimed to investigate how diabetes and hypoglycemic agents alter the levels of renal urate transporters. In insulin-depleted diabetic rats with streptozotocin treatment, both UA excretion and fractional excretion of UA were increased, suggesting that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 45 publications
5
77
1
Order By: Relevance
“…The mechanism by which nucleotide rich meal ingestion elevates circulating uric acid concentrations likely relates to increased uric acid production as a metabolic end-product without any appreciable increase in (at least over the immediate postprandial period) urinary clearance. While we did not collect urine samples to confirm this, recent animal data report that experimental alterations in circulating uric acid concentrations are regulated at the level of renal handling [18]. However, this work also suggested that the direct mechanism was the level of circulating insulin, which is not consistent with our finding of equivalent postprandial insulin responses across conditions.…”
Section: Discussioncontrasting
confidence: 87%
“…The mechanism by which nucleotide rich meal ingestion elevates circulating uric acid concentrations likely relates to increased uric acid production as a metabolic end-product without any appreciable increase in (at least over the immediate postprandial period) urinary clearance. While we did not collect urine samples to confirm this, recent animal data report that experimental alterations in circulating uric acid concentrations are regulated at the level of renal handling [18]. However, this work also suggested that the direct mechanism was the level of circulating insulin, which is not consistent with our finding of equivalent postprandial insulin responses across conditions.…”
Section: Discussioncontrasting
confidence: 87%
“…SGLT2 inhibitors have recently emerged as a promising novel class of glucose lowering drugs to facilitate glucose excretion in urine independent of insulin [35]. Accumulating data indicated their antihyperuricemic effects in both clinical [18,19,36] and basic studies [37,38]. One of basic studies performed in vitro using Xenopus oocytes indicated that luseogliflozin lowered the SUA level due to inhibition of UA reabsorption mediated by GLUT9 isoform 2 at the collecting duct of the renal tubule [38].…”
Section: Discussionmentioning
confidence: 99%
“…One of basic studies performed in vitro using Xenopus oocytes indicated that luseogliflozin lowered the SUA level due to inhibition of UA reabsorption mediated by GLUT9 isoform 2 at the collecting duct of the renal tubule [38]. Another study conducted in STZ-induced diabetic rats suggested that empagliflozin may exert anti-hyperuricemic effects via regulating URAT1 and ABCG2 [37]. However, our study demonstrated that empagliflozin promoted ABCG2 expression in kidney and ileum in KK-Ay mice with HUA, but has little impact on the other transporters.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, GLUT9 isoform 2 is expressed at the apical membrane of the kidney tubular cells and transports both uric acid (UA) and glucose. In addition, insulin increases urate transporter 1 and decreases ATP-binding cassette subfamily G member 2 levels, resulting in increased UA reabsorption 6,7 .…”
Section: Dear Editormentioning
confidence: 99%